2020
DOI: 10.3892/ijo.2020.5133
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between ETS transcription factor ETV1 and histone demethylase JMJD1A in colorectal cancer

Abstract: ETS variant 1 (ETV1) is an oncogenic transcription factor. However, its role in colorectal cancer has remained understudied. The present study demonstrated that ETV1 downregulation led to reduced HCT116 colorectal cancer cell growth and clonogenic activity. Furthermore, the ETV1 mRNA levels were enhanced in colorectal tumors and were associated with disease severity. In addition, ETV1 directly bound to Jumonji C domain-containing (JMJD) 1A, a histone demethylase known to promote colon cancer. ETV1 and JMJD1A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 118 publications
0
15
0
Order By: Relevance
“…Furthermore, blood-based NGS testing suggested lowabundance mutations (<5%) of nine newly emerged genes, indicating the emergence of tumor subcloning and heterogeneity. These genes have been previously reported to be associated with poor prognosis (21)(22)(23)(24)(25)(26)(27), but few reports on the efficacy of chemotherapy or target drugs are available. This suggests that tumors with polygenic mutations tend to be more aggressive in terms of biological behavior, leading to poor survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, blood-based NGS testing suggested lowabundance mutations (<5%) of nine newly emerged genes, indicating the emergence of tumor subcloning and heterogeneity. These genes have been previously reported to be associated with poor prognosis (21)(22)(23)(24)(25)(26)(27), but few reports on the efficacy of chemotherapy or target drugs are available. This suggests that tumors with polygenic mutations tend to be more aggressive in terms of biological behavior, leading to poor survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…ETV1 could be upregulated by BRAFV600E/MAPK pathway activation to promote cancer invasiveness and progression (38). Oh et al (39) revealed that ETV1 may regulate JMJD1A-FOXQ1 axis to drive colorectal tumorigenesis. In skin squamous cell carcinomas, upregulation of ETV1 was sufficient to induce most CAF effectors upregulated by fibroblast growth factor (FGF), which could promote the secretion of multiple chemokines with macrophagerecruiting activity including CXCL1, CXCL10, and CXCL11.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, JMJD1A can also function as a coactivator for ETS transcription factor ETV1 to promote the colorectal tumorigenesis. 28 In HeLa cells derived from cervical cancer, JMJD1A can function as a coactivator for signal transducer and activator of transcription 3 (STAT3) and promote the recruitment of STAT3 to the c-Myc gene promoter through H3K9 demethylation. Thus, JMJD1A can promote the JAK2-STAT3 signaling to promote the proliferation and motility of HeLa cells.…”
Section: Transcription Factors Regulated By Jmjd1a In Other Cancer Typesmentioning
confidence: 99%